Particularities of the use of injectables reducing localized facial fat - Pereira, Idalina Marcia (2021)
Objective: to evaluate the particularities of the use of injectables in the reduction of localized facial fat, focusing on deoxycholic acid and sodium deoxycholate, in order to analyze its efficacy and present relevant information for clinical practice. Bibliographic Review: The compounds that promote lipoclasis, deoxycholic acid and sodium deoxycholate have been used in injectable treatments to decrease fat deposits located on the face. Deoxycholic acid is a synthetic bile acid recently introduced in the field of rejuvenating therapies for the reduction of submental fat. Sodium deoxycholate is the salt of deoxycholic acid, has a detergent action and solubilizes cell membranes, induces tissue necrosis and volume reduction. Most of the studies evaluated dealt with the adiposity of the submental region, however treatments were also reported in the infrapalpebral, mandibular regions and in the regions of the middle and lower third of the face. It was observed that both substances are effective and safe, produce satisfactory results and cause slight and local adverse reactions. Conclusion: The reduction of localized fat in the face through the injection of sodium deoxycholate or deoxycholic acid has a unique action in the treatment of localized fat for inducing adipocyte necrosis and neocolagenesis.